2015
DOI: 10.5604/20834543.1186910
|View full text |Cite
|
Sign up to set email alerts
|

Goalball as an effective means of physical improvement for blind and visually impaired players

Abstract: Krzak J, Ślężyńska M, Ślężyński J. Goalball as an effective means of physical improvement for blind and visually impaired players. AbstractThe study was performed between 2002-2006 among players aged 16-18 practicing goalball in order to investigate the beneficial effects of the game on physical fitness, spatial orientation and sound localization in people with visual impairment. Substantial progress in physical fitness of all motor skills in goalball players was confirmed. Tests for visual orientation and sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 2 publications
0
5
0
1
Order By: Relevance
“…On the other hand, Aydın et al (2004) suggested that motor and physical features of goalball players with visual disabilities developed more significantly than did those of individuals with visual disabilities who do not play goalball. In another study conducted with children with visual impairments, Krzak et al (2015) put forward the idea that goalball players with visual impairments developed spatial perception and physical characteristics as a result of their participation in sport.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Aydın et al (2004) suggested that motor and physical features of goalball players with visual disabilities developed more significantly than did those of individuals with visual disabilities who do not play goalball. In another study conducted with children with visual impairments, Krzak et al (2015) put forward the idea that goalball players with visual impairments developed spatial perception and physical characteristics as a result of their participation in sport.…”
Section: Discussionmentioning
confidence: 99%
“…Anthropometric characteristics are an important factor in goalball: Height and arm and hand length of a player in the defense position seem to be closely related to goalball techniques and may influence the performance of players (Molik et al, 2015). The literature shows that researchers have mainly focused on the aerobic capacity (Gulick & Malone, 2011), spatial orientation (Krzak et al, 2015), psychological strategies (Stamou et al, 2007), the effects of the game on physical fitness (Atan & Ayca, 2015; Ayça, 2013; Aydın et al, 2004; Calışkan et al, 2006; Furtado et al, 2016; Karakaya et al, 2009; Krzak et al, 2015; Temur et al, 2014), motoric characteristics (Karakollukçu & Aslan, 2015), throwing techniques (Bowerman et al, 2011), morphological characteristics (Gualdi-Russo & Zaccagni, 2001; Scherer et al, 2012), and nonverbal communication (Gomes-da-Silva et al, 2015) in the game. However, few studies have examined the anthropometric characteristics of goalball players related to their game performance.…”
mentioning
confidence: 99%
“…Only the athletes with more than 10 years of experience had better static balance scores (p<0.05) [32]. Krzak et al (2015) reported that playing goalball provides significant enhancements on motor abilities in visually impaired individuals [33].…”
Section: Discussionmentioning
confidence: 99%
“…Using hearing to detect location is applied in playing sports, such as Goalball. For the visually impaired, the sound is important in indicating the ball's location, and avoiding possible accidents (15). However, the jingling of the bells embedded in the ball is only heard when the ball is in motion.…”
Section: Introductionmentioning
confidence: 99%